2002
DOI: 10.1079/nrr200245
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, body fat distribution and breast cancer

Abstract: Strong epidemiological data exists implicating anthropometric risk factors in breast cancer aetiology. In premenopausal women the risk of breast cancer increases with increased height, yet decreases with increasing weight and BMI. Although the evidence is not strong, a counter-intuitive positive relationship between central adiposity and premenopausal breast cancer risk is emerging. In post-menopausal women an increased risk in breast cancer has been found for all anthropometric measures: height, weight, BMI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 138 publications
(227 reference statements)
0
15
0
Order By: Relevance
“…There are several plausible biological mechanisms why body fat distribution might be a predictor of breast cancer risk. The first mechanism is that central obesity is associated with hyperinsulinaemia and insulin resistance [41,42]. A meta-analysis showed that type II diabetes is associated with increased risk of breast cancer [43], supporting this theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several plausible biological mechanisms why body fat distribution might be a predictor of breast cancer risk. The first mechanism is that central obesity is associated with hyperinsulinaemia and insulin resistance [41,42]. A meta-analysis showed that type II diabetes is associated with increased risk of breast cancer [43], supporting this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechnasim is that body fat distribution is related to hormone levels. Visceral adiposity is associated with decreased sex hormone binding globulin (SHBG) and thus unbound, bioavailable oestrogen and testosterone levels may be increased in women with central obesity [41,44–46]. The third proposed mechanism is that obesity affects breast cancer risk through inflammation and aromatase axis.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare results of these studies with each other and with ours because in some cases mice were homozygous for the neu gene or it was not indicated whether they were homozygous or heterozygous for neu. Serum factors, including estrogen, insulin, and/or IGF-I levels, are considered to be mediators of obesity's effect on postmenopausal breast cancer risk (36). One of our goals is to develop animal models to identify mechanisms to explain the body weight/breast cancer relationship.…”
Section: Discussionmentioning
confidence: 99%
“…45 Recently, interest has focused on leptin as a possible growth factor for mammary tumorigenesis. Leptin receptors are expressed in human breast tumors and breast cancer cell lines and the addition of leptin increases cell proliferation.…”
Section: Discussionmentioning
confidence: 99%